MANFAAT SENAM LANSIA TERHADAP KADAR IMUNOGLOBULIN G (IgG) - Tintin Sukartini (Universitas Airlangga, 2017)
The health problem is frequently found for elderly with age more than 55 years old. It has adverse effect on cardiovascular and Immunological system. The objective of this study was to analyze the effect of elderly exercise on the increase of fitness in Elderly. The design of this study was quasy experiment design involving two groups subject. The study took 12 respondents of elderly recruited by purposive sampling. The independent variable was elderly exercise and the dependent variable was IgG. Data were collected by laboratory test and analyzed by using t-test with significance level of a ≤ 0.05. Result showed that elderly exercise had significant effect on the IgG level (p = 0,002). Further studies are recommended on the effect of elderly exercise on the increase immunity system concerning with the role of interferon gamma.